The effect of economic growth on income inequality in the Special Region of Yogyakarta - Az zakiyyah, Nurul Azizah; Khoirudin, Rifki; Gatari, Altis Puspa (Jurnal Ekonomi & Studi Pembangunan, 2025)
This study focuses on income disparity and economic growth in the Yogyakarta Special Region. The area's slow economic expansion contributes to persistent income inequality. Using variables such as population, economic growth, district/city minimum wage, inflation, open unemployment rate, and income inequality, this study investigates the relationship between economic growth and income disparity. A quantitative approach is employed using panel data regression and Seemingly Unrelated Regression (SUR) on secondary data from the Central Bureau of Statistics (BPS). The results show that district minimum wage and open unemployment rate significantly and positively affect income inequality, while inflation, economic growth, and population size have no significant effect. These findings imply that inclusive development policies, equitable job creation, and wage regulations that consider the informal sector are essential for reducing regional income disparities in Yogyakarta.